The Expression Levels and Significance of GSH, MDA, SOD, and 8-OHdG in Osteochondral Defects of Rabbit Knee Joints. (19th January 2022) - Xiao, Zhengjun; Yu, Xuefeng; Zhang, Shuai; Liang, A.
Abstract : Objective . To observe the dynamic changes in oxidative stress and the expression levels of antioxidant and oxidative parameters in the blood and synovial fluid in the osteochondral defects of the rabbit knee joints and to explore the significance. Methods . Thirty New Zealand white rabbits were randomly selected and divided into a blank control group (n = 10 ), a model control group (n = 10 ), and an osteochondral defect group (n = 10 ). The osteochondral defect model of rabbit knee joint was constructed by medial parapatellar arthrotomy. The expression levels of glutathione (GSH), malondialdehyde (MDA), superoxide dismutase (SOD), and 8-hydroxydeoxyguanosine (8-OHdG) in peripheral venous blood and knee synovial fluid of the three groups were measured at the end of the 4th, 8th, and 12th weeks after treatment. Results . The expression levels of GSH and SOD in the blood and synovial fluid in the osteochondral defect group at the end of the 8th and 12th weeks were observably lower than those of the other two groups (P < 0.05 ); higher expression levels of MDA and 8-OHdG in the blood and synovial fluid of the osteochondral defect group compared with those of the other two groups were obtained (P < 0.05 ). At the end of the 4th, 8th, and 12th weeks, the expression levels of MDA and 8-OHdG in the blood and synovial fluid of the osteochondral defect group presented an upward trend (P < 0.05 ). Conclusion . The osteochondral defects initiate the oxidative stress in the body, which is presented as the decrease of GSH and SOD expression, and the upregulation of MDA and 8-OHdG expression.